Circulating leukocyte gene expression responses to weaning and their association with growth in holstein calves - Marta Sfulcini; Erminio Trevisi; Fiorenzo Piccioli-Cappelli; Andrea Minuti (PLoS ONE, 2026)
Weaning represents a critical transition in dairy calves, involving simultaneous dietary, social, and environmental changes. This study investigated how the weaning affects immune-related gene expression in circulating leukocytes of Holstein calves and whether post-weaning growth performance is associated with distinct immunometabolic responses. Forty female calves were retrospectively classified into two groups based on average daily gain (ADG) during the 10 days following complete weaning (from 60 to 70 days of age). Calves were fully weaned at 60 days of age using a step-down approach. Animals were categorized as high ADG (HIGH, n = 20) or low ADG (LOW, n = 20) Blood samples collected at 60 and 70 days were analyzed for plasma metabolites and leukocyte transcriptomic profiles targeting 37 genes involved in innate immunity, inflammation, oxidative stress, and metabolic regulation. Weaning induced a marked activation of innate immune pathways in all calves, as evidenced by increased expression of CD14, NFKB1, IL1β, TNFα, and genes related to cell adhesion and trafficking. However, LOW calves exhibited greater transcriptional responses, with higher expression of TLR2, CASP1, IL18, CD16, and markers of oxidative (SOD2, HSPA5) at 70 days, indicating a metabolic and transcriptional profile consistent with a greater physiological burden. Additionally, at 70 days, LOW calves had lower plasma glucose, insulin, triglycerides, and cholesterol, along with higher urea and creatinine, while β-hydroxybutyrate did not differ between groups, suggesting reduced energy availability and increased reliance on amino acid catabolism. These findings suggest that calves with lower post-weaning growth exhibit greater immune activation and altered metabolic status, highlighting variability in resilience to weaning stress. Understanding such differences may support the development of targeted nutritional or management strategies to improve early-life adaptation and long-term productivity in dairy systems